Decentralization and environmental conservation: gender effects from participation in joint forest management - Agrawal, Arun; Yadama, Gautam; Andrade, Raul; Bhattacharya, Ajoy (International Food Policy Research Institute, 2006)
This paper analyzes how women’s participation affects institutional outcomes related to the decentralized governance of community forests in Madhya Pradesh, India. The analysis is based on data from a representative sample of 641 cases of joint forest management, India’s flagship program to involve communities in forest governance. We focus on two outcomes relevant for local livelihoods: control of illicit grazing and control of illicit felling in the forest. The paper statistically estimates the effects of women’s participation on outcomes, and also the source of this effect in terms of women’s representation in committees and action in protecting forests. We find that women’s participation has substantial positive effects on regulating illicit grazing and felling, even after controlling for the effects of a range of independent variables. We also find that the “action effect” is more important than the “representation effect,” confirming some major arguments advanced by feminist environmentalists. Our statistical results are robust to different specifications and provide considerable empirical support for promoting women’s participation in community-based protection of natural resources.